Kualitas Plankton Pada Kolam Pasca Tambang Batu Bara Yang Dimanfaatkan Untuk Budidaya Perairan - Henny Pagora; Ghitarina Ghitarina; Deni Udayana (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2015)
Coal post-mining pond has been used for fish cultivation. The success of cultivation in these locations was highly dependent on environmental conditions. The environment as a place for cultivation needs attention for maximum results. One factor that needs to be attention for fish cultivation in post-mining pond is plankton, which acts as an indicator of the quality of waters. Based on identification and calculation was made known that the number of species, abundance, diversity index and uniformity index value of plankton in the post-mining pond was low enough indicated that the water conditions was infertile due to lack of nutrients content, so little of plankton species which were able to live and multiply well.